The development of switched-mode power supply for DC motor application - Ganaesan, Tevadasin (2009)
This project research is on detailed account on the control design for input tracking of a buck converter driven dc motor. Dc motor has good speed control respondence, wide speed control range. It is widely used in speed control systems which need high control requirements, such as rolling mill, double-hulled tanker, and high precision digital tools. One of the most common methods to drive a dc motor is by using PWM signals with respect to the motor input voltage. In some application dc motor require high power consumption when involves large amount of loads. Therefore the use of SMPS to supply the dc motor from ac power supply can provide the required power to the motor. SMPS can be developed by combining rectifier which convert ac-dc and buck converter which output can be supplied to the dc motor. In this research, the SMPS which supplies the dc motor is developed and the output of SMPS is controlled by using PWM.